In their Own Voices: Experiences of Dalit Students in Higher Education Institutions - Maurya, Rakesh Kumar (International Journal of Multicultural Education, 2018)
This qualitative study explores the experiences of Dalit students in one of the state universities of Uttar Pradesh in India. An Interpretative Phenomenological Analysis (IPA) was conducted to understand the experiences of Dalit students at higher education institutions, including caste-based prejudice and discrimination on campus. A total of seven themes emerged indicating caste-based prejudice and discrimination against Dalit students in both explicit and subtle ways at various levels of the university. Caste-based discrimination, humiliation, and exclusion were experienced by Dalit students at the level of fellow students, faculty, and administration.